Analisis Komparatif pendapatan inseminator pegawai negeri sipil (PNS) Dan non PNS Dikabupaten Kulonprogo - , SEPTI NUR WULAN MULATMI, Dr. Tri Anggraeni Kumastuti, SP., MP ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was aimed to analyze the inseminatorsâ income and the differences between income civil servant inseminators and non-civil servant inseminators in Kulon Progo. This research was conducted in Kulon Progo as one of the areas in the province that has the potential for development of beef cattle farming. The sample of the inseminators were taken by purposive sampling method, where as many as 24 people participants actively work. Measurements performed descriptively income in the form of a table, while the t-test was used to determine the ratio of income civil servant inseminators and non-civil servant inseminators. The results showed that the average revenue inseminators income was Rp 22.492,00 per head. The results were obtained by t test (2.50)> t table (1.717) at p <0.05 or non-civil servant inseminators income bigger than civil servant inseminators. This is because the non-civil servant inseminators have more time to do the Artificial Insemination.